2001
DOI: 10.1029/2000jd900744
|View full text |Cite
|
Sign up to set email alerts
|

Global three‐dimensional modeling of the water vapor concentration of the mesosphere‐mesopause region and implications with respect to the noctilucent cloud region

Abstract: Abstract. A global three-dimensional model of the dynamics (0-150 km) and chemistry (30-150 km) of the middle atmosphere has been developed and applied to the problem of the water vapor distribution of the mesosphere-mesopause region. The mesopause region is one of the most intricate domains of the atmosphere and requires an extraordinarily careful modeling. In order to interpret the specific feature of the water vapor distribution, particular attention was paid to the problem of the effective characteristic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 78 publications
7
101
0
Order By: Relevance
“…7) seasonal inter-hemispheric differences in the subtropics in this altitude region might be anticipated. Recently evidence of an inter-hemispheric coupling between the polar winter stratosphere and polar summer mesosphere has been presented using the mesospheric pole-to-pole circulation as the connecting link (Karlsson et al, 2007;Becker et al, 2004;Becker and Fritts, 2006;Karlsson et al, 2008). These studies suggest a stronger upwelling in the Northern Hemisphere polar summer mesosphere as compared to the Southern Hemisphere, accompanied by a stronger meridional flow towards the Southern Hemisphere winter polar region.…”
Section: Discussion and Summarymentioning
confidence: 85%
See 1 more Smart Citation
“…7) seasonal inter-hemispheric differences in the subtropics in this altitude region might be anticipated. Recently evidence of an inter-hemispheric coupling between the polar winter stratosphere and polar summer mesosphere has been presented using the mesospheric pole-to-pole circulation as the connecting link (Karlsson et al, 2007;Becker et al, 2004;Becker and Fritts, 2006;Karlsson et al, 2008). These studies suggest a stronger upwelling in the Northern Hemisphere polar summer mesosphere as compared to the Southern Hemisphere, accompanied by a stronger meridional flow towards the Southern Hemisphere winter polar region.…”
Section: Discussion and Summarymentioning
confidence: 85%
“…The simulations of WACCM used here for the tidal analysis show a phase shift that starts already at 60 km. Other models, like COMMA-IAP -Cologne Model of the Middle Atmosphere -Institute of Atmospheric Physics in Kühlungsborn, Sonnemann et al (1998), do not show any phase shift at all (Körner, 2002;Körner and Sonnemann, 2001). In comparison to the HALOE analysis of the mesospheric SAO in water vapour (Jackson et al, 1998, their Fig.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In the literature, however, values of D zz at a fixed height vary in a broad interval (up to an order of magnitude or more, see, e.g., Hocking, 1992) and are strongly dependent on latitude and season of the year (e.g., Danilov and Kalgin, 1992;Lübken 1993Lübken , 1997, whereas characteristics of vertical wind velocity w z in the mesosphere have not been measured at all and numerical models or estimates based on known theoretical relations with measured characteristics of the mesosphere are, actually, the only available source of information about them. Körner and Sonnemann (2001) demonstrated that values of the mean zonal component of vertical wind velocity reach about 1-2 cm s −1 at 80-90 km. Characteristic amplitudes of vertical wind velocity variations in diurnal and semidiurnal tides may be found from their relationship with the amplitudes of temperature variations in these atmospheric waves.…”
Section: The Procedures Of H 2 O Retrievalmentioning
confidence: 99%
“…The average temperature for September/October ranges around 260 K. This general feature is interrupted in the winter season by the so-called sudden stratospheric warmings when the polar vortex breaks down and the air can be heated up to more than 300 K. The water vapor concentration possesses a marked annual variation in mean and high latitudes characterized by a concentration peak up to more than 7 ppmv just around the stratopause/lower mesosphere occurring from August to October (e.g. Seele and Hartogh, 1999;Körner and Sonnemann, 2001;. Model calculations predict only a relatively slight dependence of the ozone concentration on temperature (according to the dependence of the reaction rates on temperature), water vapor or even on chlorine when it varies in natural borders (Frederick, 1980;Rusch et al, 1983;Solomon et al, 1983;Keating et al, 1985;Fichtelmann and Sonnemann, 1989).…”
Section: Introduction and Ozone Observationsmentioning
confidence: 99%
“…Water vapor is the main source gas for the chemically rather active hydrogen radicals which destroy catalytically odd oxygen. The effective chemical lifetime of water vapor at the stratopause, that is the lifetime which considers both the chemical loss and the chemical production (see Körner and Sonnemann, 2001 for definition), is extremely long and amounts to several months meaning water vapor is determined by transports in this domain. The hydrogen radicals formed by the photolysis of water vapor and their oxidation by O( 1 D) return to water vapor within so-called zero cycles producing only heat.…”
Section: Water Vapor Observations and Temperature Measurementsmentioning
confidence: 99%